2013
DOI: 10.1111/iwj.12199
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging patients to self‐care – the preliminary development and validation of the VeLUSET©, a self‐efficacy tool for venous leg ulcer patients, aged 60 years and over

Abstract: Venous leg ulceration has a high recurrence rate. Patients with healed or frequently recurring venous ulceration are required to perform self-care behaviours to prevent recurrence or promote healing, but evidence suggests that many find these difficult to perform. Bandura's self-efficacy theory is a widely used and robust behaviour change model and underpins many interventions designed to promote self-care in a variety of chronic conditions. By identifying areas where patients may experience difficulty in perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
1
20
0
4
Order By: Relevance
“…The evidence for internal consistency (Cronbach's α = 0·93) indicated that some of the items in the questionnaire could be made redundant. The test–retest reliability showed a strong positive relationship between test and retest scores ( r  = 0·92, P  < 0·001) at baseline and 4 weeks32.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The evidence for internal consistency (Cronbach's α = 0·93) indicated that some of the items in the questionnaire could be made redundant. The test–retest reliability showed a strong positive relationship between test and retest scores ( r  = 0·92, P  < 0·001) at baseline and 4 weeks32.…”
Section: Resultsmentioning
confidence: 93%
“…Following further qualitative research with patients and experts, items were further reduced to 60. The acceptability of the instrument in the validation phase was poor, with only 41 per cent of the data complete32. The evidence for internal consistency (Cronbach's α = 0·93) indicated that some of the items in the questionnaire could be made redundant.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations